Efficient dark fermentative hydrogen production from enzyme hydrolyzed rice straw by Clostridium pasteurianum (MTCC116) - Srivastava N.; Srivastava M.; Kushwaha D.; Gupta V.K.; Manikanta A.; Ramteke P.W.; Mishra P.K. (My University, 2025)
In the present work, production of hydrogen via dark fermentation has been carried out using the hydrolyzed rice straw and Clostridium pasteurianum (MTCC116). The hydrolysis reaction of 1.0% alkali pretreated rice straw was performed at 70 °C and 10% substrate loading via Fe3O4/Alginate nanocomposite (Fe3O4/Alginate NCs) treated thermostable crude cellulase enzyme following the previously established method. It is noticed that under the optimized conditions, at 70 °C the Fe3O4/Alginate NCs treated cellulase has produced around 54.18 g/L sugars as the rice straw hydrolyzate. Moreover, the efficiency of the process illustrates that using this hydrolyzate, Clostridium pasteurianum (MTCC116) could produce cumulative hydrogen of 2580 ml/L in 144 h with the maximum production rate of 23.96 ml/L/h in 96 h. In addition, maximum dry bacterial biomass of 1.02 g/L and 1.51 g/L was recorded after 96 h and 144 h, respectively with corresponding initial pH of 6.6 and 3.8, suggesting higher hydrogen production. © 2017 Elsevier Ltd